Implementation of The State Official Wealth Report Policy in Minahasa Regency - Supit, Anastasya Brisa; Sendouw, Recky H. E.; Mandagi, Marthinus (Technium Social Sciences Journal, 2024)
This research aims to find out, describe and analyze the implementation of the State Official Wealth Report (LHKPN) policy in Minahasa Regency, with research methods, namely qualitative description, number of informants of 5 people, and data analysis techniques using observation, interviews and documentation. It can be concluded that the process of implementing the Corruption Eradication Commission (KPK) policy No. 2 of 2020 has not been implemented well, this can be seen from the results of the research indicators as follows. Only a few government administrators are aware of the rules used in the procedures for imputing LHKPN, and not only that, it is also found that there are several state administrators who are negligent, and are often late in imputing LHKPN results data because they are confused about the procedures for online LHKPN reporting. Reporting in LHKPN reporting is not yet optimal, this is because in 2018-2022, there are still several government administrators who only report LHKPN once, and the level of negligence by Minahasa district government administrators is very high due to the lack of supervision carried out, this causes only a few who are active in LHKPN reporting for the 2018-2022 period. Results from 208 state administrators in Minahasa Regency, only 101 state administrators reported LHKPN, and of those 101 there were 45 state administrators whose LHKPN report data was inaccurate.